MicroRNAs in the key events of systemic lupus erythematosus pathogenesis - Husakova, Marketa (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2016)
BACKGROUND: Small non-coding RNA molecules (miRs) are involved in immune cell maturation and function and might influence immunopathological processes of systemic lupus erythematosus (SLE) pathogenesis. METHODS AND RESULTS: This paper presents the results of a literature search for publications dealing with the relationship between miRs and pathological factors related to SLE such as genetic background, immune dysregulation and gender-associated differences participating in SLE development. In SLE, distinct miRs are differentially expressed in SLE cells of innate and adaptive immunity. The miR-146a and miR-155 genes, among others, interfere with intracellular signalling pathways downstream of toll-like receptors 7 and 9 (TLR- 7, TLR-9) and influences interferon (IFN)-type I synthesis in plasmacytoid dendritic cells. In T and B cells, miR-126, miR-21, miR-146a, miR-155, miR-1246 and others might influence gene expression by epigenetic modifications, support abnormal cytosine release, differentiation of cell subsets, B cell hyperactivity and autoantibody production. Besides, estrogen might up- and downregulate immunologically active miRs, which are potential mediators of hormonal influences in SLE development. Moreover, SLE genetic basis included some polymorphisms of the miR-146a gene, which varies across populations. CONCLUSION: Distinct miRs are differentially expressed in both SLE mice models and human patients and promote autoimmune features of immune processes. MiRs are important molecules modulating susceptibility to SLE as well as its onset, clinical diversity and progression.
Keywords: Genetic Predisposition to Disease; T-Lymphocytes; estrogeny; jednonukleotidový polymorfismus; estrogen; Immunity, Innate; mikro RNA; genetic predisposition; Disease Models, Animal; T-lymfocyty; innate immunity; Mice; systémový lupus erythematodes; MicroRNAs; přirozená imunita; B-lymfocyty; Adaptive Immunity; modely nemocí na zvířatech; zvířata; B-Lymphocytes; Humans; microRNA; Estrogens; adaptive immunity; Lupus Erythematosus, Systemic; myši; SLE; genetická predispozice k nemoci; adaptivní imunita; lidé; Polymorphism, Single Nucleotide; Animals